'BY THE IMPRESSION OF MY SEAL'. MEDIEVAL IDENTITY AND BUREAUCRACY: A CASE STUDY. (16th September 2020) - Hoskin, Philippa M; New, Elizabeth A
Abstract : This paper presents the results of a case study of wax seals dated between 1225 and 1250 from St Ethelbert's Hospital, Hereford. When medieval matrices were impressed into soft wax, handprints were often left on the reverse of the seal. The use of modern forensic techniques to capture and compare these prints provides evidence about the process of sealing and its relationship to the individual matrix owner. Seals with the same print on the reverse could be impressed with different matrices, and impressions of the same matrix have different prints on the reverse. The impressing of the matrix was not, then, as has been claimed, the responsibility of the matrix owner as the only way to impress their identity into the wax. This evidence allows a reappraisal of administrative developments in sealing, and the separation of the process of sealing from both the performance of livery of seisin and the seal owner.